Elastic, structural and optical properties of (80-x)TeO₂- x BaO-20ZnO and xAg₂O-(35- x)[0.5MoO₃-0.5v₂O₅]- 65TeO₂ glasses / Muliana Ismail - Ismail, Muliana (2016)
In this study, two series o f tellurite based glass with composition (80-x)TeO2-20ZnOxBaO (x = 0 mol% to 20 mol%) and xAg2 0 -(3 5 -x )[ 0 .5Mo0 3 -0 .5V20 5]-6 5Te0 2 (x = 0-2 5 mol%) glasses were prepared using melt-quenching method to investigate their elastic, structural, thermal and optical properties. For (80-x)TeC>2-20ZnC)-xBaC) glass samples, BaO addition resulted in a decrease in ultrasonic velocities and independent elastic moduli; this result indicated that the rigidity o f the glass network weakened possibly because non-bridging oxygen increased. Thermal analysis results showed that glass transition temperature (Tg) increased as BaO content increased because o f the stabilizing effect o f Ba2+ on the glass network. Additional analyses using bulk compression and ring deformation models revealed that the ratio between theoretical bulk modulus and experimental bulk modulus increased; this result indicated that the compression mechanism mainly involved isotropic ring compression. Furthermore, the increase in non-bridging oxygen formation with BaO addition caused a decrease in optical energy gap CEopt) and an increase in refractive index (n). An increase in Urbach energy (Eu) indicated that the degree o f disorder in the glass system also increased. For xAg2 0 -(3 5 -x )[ 0 .5Mo0 3 -0 .5V20 5 ]-6 5Te0 2 glass, ultrasonic velocities showed nonlinear behaviors, wherein the velocities increased for x < 1 0 mol% and then decreased beyond x = 10 mol%. Independent elastic moduli and other related moduli, and Tg also showed similar nonlinear behaviors with maxima at x = 10 mol%. This result coincided with the electronic-to-ionic transition region as previously reported. A large decrease in elastic moduli beyond x = 1 0 mol% indicated a decrease in stiffness, thereby enabling ionic conductivity. Although Ag2 0 addition weakened the glass network, the presence o f M0O3 played an important role as an additional glass former at x < 10 mol% apart from V2O5. Analysis o f bulk compression and ring deformation models showed a large decrease at x < 1 0 mol% followed by near constancy with increased Ag2 0 content. These results showed that ring deformation was reduced in the electronic region, but limited ring deformation took place in the ionic region, and that the main compression mechanism was mainly isotropic ring compression. The £opt and n showed a slope change at x = 1 0 mol%, which confirmed the effect o f mixed electronic-ionic conductivity on optical properties.